Indoor air quality investigation before and after relocation to WELL-certified office buildings. (15th October 2021) - Licina, Dusan; Langer, Sarka
Abstract: Air pollutant exposure in workplace environments has been associated with health and cognitive outcomes of workers. While green building certification programs have been instrumental in promoting indoor air quality (IAQ), the present literature indicates inconsistent evidence. Recent emergence and proliferation of WELL certification program that prioritizes human health has evoked new questions about its effectiveness in relation to IAQ. To investigate the effectiveness of the WELL certification, we have quantitatively compared IAQ results before and after relocation to two WELL-certified office buildings using the same cohort of occupants. Physical measures included integrated samples of TVOC, individual VOC, formaldehyde and acetaldehyde, NO2, SO2, O3 and longitudinal records of CO2 and size-resolved particles. Complementary survey responses about satisfaction with IAQ and thermal comfort were collected from ~250 employees. For the majority of air pollutants, there was no significant concentration difference between non-WELL and WELL buildings, but not always. The WELL-certified buildings had substantially higher levels of TVOC and individual VOC associated with paints, especially shortly after the relocation. However, there was statistically significant improvement in IAQ satisfaction after relocation into WELL buildings regardless of the air pollution levels, possibly confounded by thermal environment, awareness of the WELL certification or other non-measurable factors. Highlights: The results of this study aim to inform the continuous evolution of human-centric green building certification programs. Occupants of WELL-certified buildings are more satisfied with IAQ compared to BREEAM-certified or non-certified buildings. Physical measures of IAQ in WELL buildings are equal relative to other buildings or inferior for certain VOCs. Future work should adopt larger statistical power to probe the links between various features of WELL certification and IAQ.